On the Representation of Androgynous Figures in the Renaissance Art - Redondo, Jordi (2020)
La antigua idea de la androginia –una variante del mito de la metamorfosis– transmitía en la opinión de los pensadores renacentistas las ideas de perfección y plenitud, como medio para superar la oposición de las naturalezas femenina y masculina. El presente trabajo muestra el origen del motivo y su desarrollo según los intereses, creencias e inquietudes de teólogos y pensadores, por un lado, y artistas, por otro.
For Renaissance thinkers, the ancient idea of the androgyny –a variant of the metamorphosis’ myth– conveyed the ideas of perfection and completeness, as a way to overcome the opposition of the female and male natures. This paper shows the origin of the motif and its development according with the interests, beliefs and concerns of theologians and thinkers, from the one hand, and artists on the other.
Keywords: Metamorfosis; Androginia